Analisis Strategi Bisnis dalam Menghadapi Persaingan pada Toko Harga Pas di Kabupaten Dharmasraya - Dian Afriana; Habibatur Ridhah (ARZUSIN, 2026)
Although business strategy analysis and sharia business principles have been widely discussed in previous studies, research that specifically integrates Porter’s Five Forces analysis with sharia-based business strategies in local retail businesses remains limited. This study aims to analyze the condition of business competition, the business strategies implemented, and their conformity with sharia business principles at Toko Harga Pas in Dharmasraya Regency. This study employed a qualitative approach with a case study design, involving informants consisting of the owner, employees, and customers selected through a purposive sampling technique. Data were collected through interviews, observation, and documentation, and were then analyzed using the interactive analysis technique of Miles and Huberman. The findings showed that the condition of business competition was at a competitive level, marked by a high threat of new entrants, strong buyer bargaining power, and pressure from digital-based substitute products. The business strategies implemented focused on setting competitive prices, improving service, and maintaining customer trust. These findings contribute to the development of Porter’s Five Forces theory in the context of local retail and broaden understanding of the integration of business strategy and sharia principles. The conclusion of this study confirms the importance of adaptive and customer-oriented strategies in facing business competition, and encourages business actors to increase innovation and the use of technology. The implications of this study include theoretical contributions in the field of strategic management and practical implications for retail business actors, while also opening opportunities for further research related to digitalization in retail business strategy.